THE FIBER DIAMETER OF SYNTHETIC BIORESORBABLE EXTRACELLULAR MATRIX INFLUENCES HUMAN FIBROBLAST MORPHOLOGY AND FIBRONECTIN MATRIX ASSEMBLY - Hsia, Henry C. (2011)
BACKGROUND: The ideal scaffold material should provide immediate capacity to bear mechanical loads, while also permitting eventual resorption and replacement with native tissue of similar mechanical integrity. Scaffold characteristics such as fiber diameter provide environmental cues that can influence cell function and differentiation. In this study, the impact of fiber diameter of scaffolds constructed from a tyrosine-based bioresorbable polymer on cellular response was investigated. METHODS: Electrospun bioresorbable poly(DTE carbonate) scaffolds comprised of microfibers or nanofibers were constructed and seeded with human dermal fibroblasts. The impact of fiber diameter on actin cytoskeletal morphology, focal adhesion size, fibronectin matrix assembly, and cell proliferation were evaluated using immunoflurorescent microscopy and computer-assisted image analysis. RESULTS: Actin stress fibers were more easily observed in cells on microfiber scaffolds compared to those on nanofiber scaffolds. Cells on nanofiber scaffolds developed smaller focal adhesion complexes compared to those on microfiber scaffolds (p<0.0001). The temporal patterns of fibronectin matrix assembly were affected by scaffold fiber diameter with cells on microfiber scaffolds showing a delayed response in dense fibril formation compared to nanofiber scaffolds. Cells on nanofiber scaffolds showed higher proliferation compared to microfiber scaffolds at time points under 1 week (p<0.01), but by 2 weeks significantly higher cell proliferation was observed on microfiber scaffolds (p<0.01). CONCLUSIONS: The fiber diameter of bioresorbable scaffolds can significantly influence cell response and suggest that the ability of scaffolds to elicit consistent biological responses depend on factors beyond scaffold composition. Such findings have important implications for the design of clinically useful engineered constructs.